2019
DOI: 10.1016/j.fuproc.2019.106179
|View full text |Cite
|
Sign up to set email alerts
|

Progress of acetone-butanol-ethanol (ABE) as biofuel in gasoline and diesel engine: A review

Abstract: The properties of butanol offer more promising results compared to those of lower chain alcohol such as methanol or ethanol. However, butanol as a biofuel has not yet been commercially produced due to its costly process. Butanol is generally produced via the process of Acetone-Butanol-Ethanol (ABE) fermentation and can only be acquired after it was recovered from the ABE solvent. Despite the efforts and recent developments, obtaining higher butanol concentration from ABE fermentation is still relatively expens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(38 citation statements)
references
References 237 publications
(344 reference statements)
1
36
0
1
Order By: Relevance
“… Benajes et al (2017a, 2017b), Çelebi and Ayd (2019), Masimalai and Subramaniyan (2019), Veza et al (2019)…”
Section: Figurementioning
confidence: 99%
“… Benajes et al (2017a, 2017b), Çelebi and Ayd (2019), Masimalai and Subramaniyan (2019), Veza et al (2019)…”
Section: Figurementioning
confidence: 99%
“…Internal combustion engines running on next-generation biofuels is the thrust area amongst the research community. Studies on bio fuelled engines showed improved performance, significant drop in CO emissions, unburned hydrocarbons, and particulate matters [8][9][10][11][12][13][14][15][16][17][18]. There can be no single best suggestive biofuel for the engine.…”
Section: Gepmentioning
confidence: 99%
“…Feasibly, photosynthesis could transform 6.7 % of the solar energy production on land into chemical energy, although only 0.3 % is retained as carbon compounds in land plants on average [26]. Bioethanol synthesized from carbohydrates and biodiesel (ester) derived from fats and oils is currently the most popular fuels [27]. While ethanol is obtained from starch and sugars, it makes a good impact from the perspective of protecting the natural environment.…”
Section: Bio-fuel Sources/productionmentioning
confidence: 99%